Sensitivity of varve biogenic component to climate in eastern and central Finland - Salminen Sarianna; Saarni Saija; Saarinen Timo (SPRINGER, 2026)
Biogenic varves as well as the biogenic component of clastic-biogenic varves have great potential as climate and environmental proxies but the response of biogenic lamina thickness to variations in growing-season climate is not well known. The connection of biogenic lamina thickness with growing-season or open-water season climate has been the focus of a limited number of studies. We examined biogenic laminae deposited during the past 100 years in five Finnish lakes representing different catchment types. We compared variations in biogenic lamina thicknesses with growing-season temperature records and open-water-season precipitation records. Statistical analyses for the whole study period reveal that the studied lakes generally respond positively to variations in growing-season temperature and open-water season precipitation. This suggests that warm summers intensify primary production while precipitation enhances transportation of allochthonous biogenic material and nutrients into the lake. Both mechanisms lead to enhanced biogenic lamina thickness. Two lakes reveal a more complex relationship to climate. Biogenic lamina thicknesses record a distinguishable climate signal despite human activities in the catchments, such as peatland drainage and forest cutting. We conclude that variations in biogenic lamina thickness of such boreal (clastic)-biogenic varves show potential for growing-season climate reconstructions. However, the response of each lake to climate parameters should be tested and understood separately.